2019
DOI: 10.1111/pim.12661
|View full text |Cite
|
Sign up to set email alerts
|

Infection by Leishmania (Leishmania) infantum chagasi causes intestinal changes B‐1 cells dependent

Abstract: Evaluating the histopathological and morphometric changes caused by Leishmania (Leishmania) infantum chagasi infection either in the presence or absence of B‐1 cells. Wild‐type Balb/c and XID mice were used. Half of XID mice received B‐1 cells adoptive transfer (XID + B1). Five animals from each group were infected (Balb/c I, XID I and XID + B1 I), totalizing six groups (n = 5). After 45 days of infection, the ileum was collected for histological processing and analysis. After infection, the XID animals showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A study revealed that BALB/c mice inoculated intravenously with amastigotes of L. infantum (chagasi) exhibited atrophy of the ileum wall after 45 days of infection. (32) In addition, hamsters and mice inoculated with other species of Leishmania also revealed morphometric changes in the IT. (23,24) Alterations in the ENS have been described in other infections.…”
Section: Discussionmentioning
confidence: 97%
“…A study revealed that BALB/c mice inoculated intravenously with amastigotes of L. infantum (chagasi) exhibited atrophy of the ileum wall after 45 days of infection. (32) In addition, hamsters and mice inoculated with other species of Leishmania also revealed morphometric changes in the IT. (23,24) Alterations in the ENS have been described in other infections.…”
Section: Discussionmentioning
confidence: 97%
“…It was also demonstrated that the infection induces differences in intestinal compartment from mice. While BALB/c mice present decrease in the thickness of the submucosa and circular layer, BALB/Xid mice present increased thickness in those sites, but the repopulation with B-1 reduces the increase index in these mice (Figure 2A) (Souza et al, 2019). Besides that, the infection also caused impaired quantitative goblet cells change, in the sialomucins and sulphomucins-producing goblet cells and in the number of Paneth cells (Figure 2A) (Souza et al, 2019).…”
Section: The Role Of B-1 Cell During Leishmania Infantum Infectionmentioning
confidence: 97%
“…The effect of Leishmania infection in the gastrointestinal tract is the topic of studies that evaluated different segments of the intestine of dogs (Figueiredo et al, 2014;Silva et al, 2016;Silva et al, 2018) and rodents (Souza et al, 2019;Lewis et al, 2020;Passos et al, 2020) with visceral leishmaniasis (VL). In human VL, the presence of amastigote forms in intestinal tissues may be related to episodes of diarrhea (Baba et al, 2006;Soria Loṕez et al, 2016;Raina et al, 2017) or not (Chattopadhyay et al, 2020).…”
mentioning
confidence: 99%